Instructor-Led VR training in medical emergency rescue education for road traffic accidents: a questionnaire-based study - Zhe Li; Guozheng Qiu; Wan Chen; Lei Shi; Yutao Tang; Guoqing Qin; Jingshu Mo; Liwen Lyu (Scientific Reports)
Abstract The application of Virtual Reality (VR) in medical emergency training, particularly in road traffic accident (RTA) management, remains underexplored. While VR offers immersive and dynamic learning environments, the effectiveness of instructor-led VR training in large-scale, emergency medical education is not yet fully understood. This study aimed to evaluate the effectiveness of instructor-led virtual reality (VR) training in medical emergency rescue education, particularly in the context of road traffic accidents. Effectiveness was assessed through participant satisfaction, perceived engagement, and self-reported learning outcomes. A cross-sectional survey was conducted among 300 emergency medical professionals who attended one-hour instructor-led VR sessions delivered through a series of workshops. Participants completed a post-training questionnaire consisting of Likert-scale items assessing course design, content practicality, clarity of instruction, VR interest, and overall satisfaction. Quantitative data were analyzed using regression and mediation analyses to identify the predictors of overall evaluation scores. Regression analysis identified course practicality (Estimate = 0.131, P < 0.001) and VR interest (Estimate = 0.357, P < 0.001) as the strongest predictors of overall satisfaction. Mediation analysis revealed that the effect of course practicality on satisfaction was partially mediated by VR interest (mediation effect = 32.5%). Participants consistently rated the sessions highly, with an overall evaluation score of 4.82 ± 0.35 out of 5. Sentiment analysis of 227 qualitative responses indicated 70.67% expressed positive opinions, particularly on the engaging and practical aspects of the VR-based approach. While the findings support the potential of instructor-led VR to enhance learner engagement and comprehension in high-stakes scenarios, limitations include the cross-sectional design and lack of long-term follow-up. Instructor-led VR training appears to be a practical, engaging, and scalable method for emergency medical education. Future research should assess its long-term impact on skill retention and real-world application.